Mobile application for the timely detection of potential COVID-19 infections - Carrasco Teran, Wilson Fernando (2022)
The objective of this study is to determine user acceptance of a mobile application for the timely detection of possible COVID-19 infections in the city of Cajamarca. For this purpose, the mobile application Covid Alerta (Covid Alert) was developed for devices with the Android operating system. The OpenUp software development methodology was used for the development of this application. The applied, quantitative, exploratory research used 2 survey forms: one to measure how the detection of COVID-19 was carried out in the city of Cajamarca, and another to measure the impact of using a mobile application to detect infected contacts. The results indicated that the most reliable screening tests are molecular tests; in addition, 85% of respondents felt much safer receiving alerts of infected contacts on their mobile devices. Likewise, 88.5% indicated confidently that the application complies with registering and reporting infected contacts. This shows that 88.8% of users accepted the use of mobile applications for the timely detection of possible COVID-19 infections.